Speech Acts Found on Joseph Story in the Translation of Sura Yusuf by Yusuf Ali - Oktian Ningsih (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This study focuses on analyzing speech acts on Joseph story using speech acts theory proposed by John R. Searle. Speech Acts is part of pragmatics and discourse analysis related to the context of speech that refers to assertive, directive, commissive, expressive, and declarative speech acts. Joseph story is part of sura Yusuf which has 111 verses, which is the best story in the Qur'an. Therefore, it contains many speech acts. Based on this, research on speech acts in Joseph story needs to be done. There are two problems with this study: what types of speech acts are found on Joseph story? And what is the mostly used type of speech acts on Joseph story?This study aims to describe speech acts using Searle's theory. Data in the form of speech on Joseph story in the form of written text, which is then analyzed using qualitative descriptive methods.The results showed the types of speech acts found on Joseph story. They are assertive, directive, commissive, expressive, and declarative. Assertive as many as 31 data, directive as many as 29 data, commissive as many as 11 data, expressive as many as 9 data, and declarative as much as 1. Assertive is the mostly used type of speech acts on Joseph story.